Financial Restatement Period: Internal and External Auditing Mechanism - Elfina Astrella Sambuaga; Chelsea Chen; Jeanette Yovanka; Kristina Fransiska (The Indonesian Journal of Accounting Research, 2021)
The purpose of this study is to empirically scrutinise the effects of audit quality, audit report lag, and audit committee characteristic towards the length of financial restatements. The population analysed in this study involved companies listed on the Indonesia Stock Exchange from 2016 to 2018. Purposive sampling technique was employed in this research, and the total sample was 153 observations. Multiple regression analysis indicates that audit quality, audit report lag, and audit committee characteristic are statistically significant toward the length of financial restatements. The audit committee characteristic and audit report lag compress the length of financial restatements, while the audit quality extends the length of financial restatements.